A comparative in vitro and in vivo study on bone tissue engineering potential of the collagen/nano-hydroxyapatite scaffolds loaded with ginger extract and curcumin. (June 2022) - Khodabandeh, Zahra; Tanideh, Nader; Aslani, Fatemeh Sari; Jamhiri, Iman; Zare, Shahrokh; Alizadeh, Narges; Safari, Anahid; Farshidfar, Nima; Dara, Mahintaj; Zarei, Moein
Abstract: Tissue engineering, a multidisciplinary science which can be used to restore the functions of the damaged tissues and organs, has attracted attention of researchers for the last decades. In this study, due to the importance of the role of scaffold in tissue engineering, optimized collagen-hydroxyapatite (COL-HA) scaffolds have been loaded with different amounts of curcumin (CUR) and hydro-alcoholic ginger extract (GIN) for bone tissue engineering applications. The scaffolds were created by freeze dryer method and the physical and biological properties of the scaffolds were evaluated in vitro and in vivo. The comparison revealed the efficacy of resulting porous 3D structures in both groups of scaffolds with CUR and GIN. Mechanically, CUR increased the tensile strength of the scaffolds, while GIN slightly decreased it. Both CUR and GIN caused higher bioactivity and osteogenesis ability in the COL-HA scaffolds. In vitro biocompatibility, in the presence of mesenchymal stem cells derived from synovial membrane of rats, has been improved by CUR and GIN. In vivo biocompatibility, by subcutaneous implantation of the scaffold in rat animal models for 12 weeks, indicated less inflammatory reactions by the addition of CUR and GIN into the scaffolds. These findings make promising appropriate scaffolds for bone tissue engineering applications. Graphical Abstract: ga1